Formation and prevention of pipe scale from acid mine drainage at iron Mountain and Leviathan Mines, California, USA. (April 2020) - Campbell, Kate M.; Alpers, Charles N.; Nordstrom, D. Kirk
Abstract: Pipelines carrying acid mine drainage (AMD) to treatment plants commonly form pipe scale, an Fe(III)-rich precipitate that forms inside the pipelines and requires periodic and costly cleanout and maintenance. Pipelines at Iron Mountain Mine (IMM) and Leviathan Mine (LM) in California carry acidic water from mine sources to a treatment plant and have developed pipe scale. Samples of scale and AMD were collected from both mine sites for mineralogical, microbiological, and chemical analysis. The scale mineralogy was primarily schwertmannite with minor amounts of poorly crystalline goethite. Although the bulk composition of the scale was similar along the length of the pipeline at IMM, the number of iron-oxidizing bacteria and concentrations of associated trace elements decreased along the flow path inside the pipeline. Laboratory batch experiments with unfiltered AMD from IMM and LM showed that Fe(II) oxidation was driven by microbial activity when the pH was <5. A remediation strategy of decreasing the pH to <2.2 was tested through geochemical modeling and laboratory experiments. These experiments indicated that scale formation could be prevented by decreasing the pH, which could be achieved at IMM by mixing source waters. However, the presence of Fe(III)-rich scale in a pipeline buffers the pH to higher values that may affect the efficacy of this remedial approach. Highlights: Precipitate forms in pipelines carrying acid mine drainage, causing costly maintenance requirements. Scale samples collected from acid mine drainage pipelines at two mine sites were composed primarily of schwertmannite. Trace elements, including Al, As, Cu, V, and Zn, accumulate in pipe scale. Scale formation was driven by microbial Fe(II) oxidation at pH values < 5. Modeling and laboratory experiments indicate that scale formation can be prevented by decreasing the pH to <2.2.